2017
DOI: 10.4103/0366-6999.198917
|View full text |Cite
|
Sign up to set email alerts
|

Association between Genetic Variants of Transforming Growth Factor-β1 and Susceptibility of Pneumoconiosis

Abstract: Background:Transforming growth factor-beta 1 (TGF-β1) and gene variants have been extensively studied in various human diseases. For example, TGF-β1 polymorphisms were associated with fibrosis and pneumoconiosis, but the data remained controversial. The aim of this meta-analysis was to assess the association between TGF-β1 −509 C>T [rs1800469], +869 T>C [rs1800470], and +915 G>C [rs1800471] polymorphisms and pneumoconiosis.Methods:A comprehensive literature search was conducted through searching in PubMed, Emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
(56 reference statements)
1
5
0
2
Order By: Relevance
“…The expression levels of the three related genes in the experimental groups increased, but their peak values appeared in different stages. In this study, the fact that the peak expression of collagen type I and III occurred after the peak expression of TGF-β1 indicated a possible causal relationship between these proteins: the total level of TGF-β1 secreted by BALF cells and lung tissues activated the expression of collagen type I and III, which was supported by the finding of previous studies 22 , 28 . This study also showed a different pattern of expression for collagen type I and III.…”
Section: Discussionsupporting
confidence: 88%
“…The expression levels of the three related genes in the experimental groups increased, but their peak values appeared in different stages. In this study, the fact that the peak expression of collagen type I and III occurred after the peak expression of TGF-β1 indicated a possible causal relationship between these proteins: the total level of TGF-β1 secreted by BALF cells and lung tissues activated the expression of collagen type I and III, which was supported by the finding of previous studies 22 , 28 . This study also showed a different pattern of expression for collagen type I and III.…”
Section: Discussionsupporting
confidence: 88%
“…Previous research has described increased levels of inflammatory serum markers in silica exposed subjects 8 , 15 . It has been observed that the presence of different polymorphisms, alongside with TNF, IL-1RA and TGF-β1 16 – 18 confer a higher risk of disease, and that levels of TNF-α show an increase before the development of a clinically recognised silicosis 19 and that are associated with disease severity. Likewise, diverse studies associate TGF-β1 levels with disease progression and show that IL-2R can be a good indicator of silicosis-associated immunological alteration.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies suggest that inflammatory processes play a key role in pneumoconiosis, which in turn promotes fibrosis progression. [ 68 , 69 ] The targets identified by omics are primarily focused on inflammatory signaling pathways relating to the immune system. When dust settles in the lungs, it activates an immune response.…”
Section: Future Research Prospectsmentioning
confidence: 99%